Recent progress in tactile sensing and sensors for robotic manipulation: can we turn tactile sensing into vision?1. (18th July 2019) - Yamaguchi, Akihiko; Atkeson, Christopher G.
Abstract : This paper surveys recently published literature on tactile sensing in robotic manipulation to understand effective strategies for using tactile sensing and the issues involved in tactile sensing. It consists of a brief review of existing tactile sensors for robotic grippers and hands, review of modalities available from tactile sensing, review of the applications of tactile sensing in robotic manipulations, and discussion of the issues of tactile sensing and an approach to make tactile sensors more useful. We emphasize vision-based tactile sensing because of its potential to be a good tactile sensor for robots. GRAPHICAL ABSTRACT: